(Nk@^UK (B- (NkAJNARDVIJSKIJ MIR (B1774 (NGODA (B:s ((NEGO PODGOTOWKA I ZAKL@^ENIE(B) /s - (NdRUVININA(B, (Ne(B.(Ni(B.s; (NaKADEMIQ NAUK sssr(B.s (NiNSTITUT ISTORIIs ((NmOSKW(Ba :s (NiZD(B. (NaKADEMII nAUK sssr(B,s, 1955)
(NzAKL(B.: (NS(B. 334-337s
(NpRILOV(B.: (NS(B. 338-365s
Keywords: (NiSTORIQs